Applying the Ulū al-Albāb approach in sustaining knowledge transfer capability among ICT firms in Malaysia - Mhd. Sarif, Suhaimi; Ismail, Yusof (2013)
This paper explores the application of Ulū al-Albāb approach in sustaining knowledge transfer capability among ICT firms in Malaysia. The Ulū al-Albāb or men of understanding emphasises on seeking the Pleasure of Allah (mardhat Allah) through the obligations as servant (‘ibād al-Rahmān) and vicegerent of Allah (khālifah Allah fi al-ard). The framework of the study integrates knowledge-based view (KBV) with Ulū al-Albāb approach as basis to sustain knowledge transfer capability among ICT firms. This framework contributes the spirituality dimension into KBV framework to sustain intellectual contribution in terms of knowledge stocks, social network and firm environment to the knowledge transfer capability among managers and knowledge workers of ICT firm in Malaysia. Knowledge is important because it enables a firm to be innovative in terms of producing new products and services to the market. Innovative firms create knowledge continuously to meet the fast changes of customers‘ preferences and their technology usage. The literature of strategic management and knowledge management suggests a firm with knowledge transfer capability is more innovative and capable of achieving sustainable competitive advantage. However, based on personal interviews with 12 informants, the study observed that Malaysia ICT firms were not well equipped with knowledge transfer capability due to over emphasized on profit-making instead of building capacity on knowledge creation, transfer and utilization. These firms need to change from where they are now to more knowledge oriented approach if they want to sustain in the ICT industry. The informants were convinced with the Ulū al-Albāb approach in sustaining knowledge transfer capability among ICT firms. However, the existing knowledge transfer capability framework needs a revision to fit the Ulū al-Albāb approach.